The Day Trader's Manual: Theory, Art, and Science of Profitable Short-Term Investing. - Liaw, K. Thomas; Eng, William F. (Journal of Finance, 1995)
THE THEORY OF DAY TRADING. Time, Price, and the Day Trader. Strategies for Profitable Day Trading. Day Trading Approaches Defined by Market Action. Chaos Theory and the Day Trader. THE SCIENCE OF DAY TRADING. Tape-Reading Techniques. Spread Trading. Trading Market Profile. Using Chart Patterns. Mathematical Approaches to Day Trading. Sequential Patterns in Day Trading. Elliott Wave Theory and Day Trading. THE ART OF DAY TRADING. Cases. Appendix. Bibliography. Index.